SERAPAN KARBONDIOKSIDA (CO2) JENIS-JENIS POHON DI TAMAN BUAH "MEKAR SARI" BOGOR, KAITANNYA DENGAN POTENSI MITIGASI GAS RUMAH KACA - Hidayati, N.; Reza, M.; Juhaeti, T.; Mansyur, M. (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTCarbondioxide (CO2) Absorption by Trees in "Mekar Sari" Fruit Garden, Bogor, in Relationto Green house Gases Mitigation. Biological diversity can make a significant contribution toreducing the build-up of greenhouse gases in the atmosphere. A biological diverse tropicalforest with a diverse plant species typically stores 50 times more carbon per unit area comparedto monoculture plantation replacing it. Thus, the trees in forests have an essential role in thefunctioning of the terrestrial biosphere, especially in the carbon cycle. Yet wild tree photosynthesesare poorly studied than crop photosynthesis for several reasons: the large number ofspecies; difficulty in measuring photosynthesis of entire trees or of forest stands. This researchaims to assess the contribution of biological diversity in CO2 absorption by analyzing thephysiological characteristics (photosynthesis, transpiration, stomatal conductance, leaf chlorophyllcontent) of tree species in "Mekar Sari" fruit garden, Bogor. The results will provideinformation on carbon sequestration of some tree species suitable for revegetation. Variance inCO2 assimilation rate is large among trees species. The results showed that there was a widerange of variation of CO2 assimilation rate between tree species. The overall CO2 assimilationrate ranged 2.33 - 13.42 ?molm-2s-1. The highest was Matoa (13.42 molm-2s-1 ) , followed byKacapi (12.50 ?molm-2s-1), Durian (11.00 ?molm-2s-1) and Nangka (11.00 ?molm-2s-1). Transpirationrate was recorded between 4.29 - 9.50 molm-2s-1. The rate of CO2 assimilation wasaffected by incident radiation and thus the quantum leaf (Q leaf) as well as leaf chlorophyllcontent. Correlation between CO2 assimilation and Q leaf under certain environmental conditionwas considerably high. Variance in stomatal conductance and transpiration rate variedamong tree species and were related to light intensity.Key words: Photosynthesis, CO2 absorption, trees